Correlation between Stress and Empathy in Medical Students As Compared To General Population - Kinjal Mehta; Prakash Patel; Swati Patel; Ajay Pawar (Medsci Publications, 2021)
Background: Medical students are exposed to numerous internal and external pressures exerted by the environment which may affect their empathy towards patients. This study was conducted to find association between perceived stress and empathy. Methodology: The study was conducted in Surat, Gujarat, India from August 15 2021 to September 15 2021 among 225 participants using perceived stress score and using the Toronto Empathy Questionnaire. Two groups -Undergraduate medical students and general population were compared. Results: Out of 160 medical undergraduates and 65 people from general population below average empathy was noted in total 51.1%. High empathic attitude was noted in general population in comparison to other medical undergraduates. 24.4% reported low stress, 64% moderate stress and 11.6% high stress and we can appreciate that low stress scores were calculated in general population in comparison to medical undergraduate students. A weak negative correlation between empathy and perceived stress was calculated in medical students whereas strong positive correlation between empathy and perceived stress was calculated in general population. Conclusion: A significant proportion of medical students had a comparatively higher stress scores and decreased empathy hence their stress is considered distress whereas general population's high stress scores were corelating to high empathic attitude, therefore their stress can be considered eustress.